The Process Of Muja Sumbang Ceremony Among Kaharingan Hindus In Papar Pujung Village, West Lahei Sub-District, North Barito Regency - Malia; Mitro; Megawati Megawati (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2024)
Muja Sumbang comes from the Dayak language of Dusun Malang in Lahei Barat regency, North Barito district. Muja Sumbang is composed of two words, "Muja," which means mantra worship, and the word "Sumbang," which means wrong view. Thus, Muja Sumbang is the worship of God/Jus Tuha Alah Talla, his manifestations, and his ancestors to ask for forgiveness and protection for the occurrence of false marriages between male and female couples. According to the beliefs of the Kaharingan Hindu community in Papar Pujung Village, Lahei Barat District, North Barito Regency, this marriage is not appropriate or should not be performed because this marriage occurs when a woman is pregnant out of wedlock and a man and woman live together without marital status. If the marriage goes ahead, the man and woman must perform the ceremony in accordance with local customary law. According to the beliefs of the Kaharingan Hindu community in Papar Pujung, Lahei Barat District, North Barito Regency, the Muja Sumbang ceremony is an attempt to purify the couple physically and mentally and to restore the balance of nature that has been created or disturbed by the couple's deviant behavior.